Determinants of Fintech Usage among University Students: The Roles of Personal Financial Management, Consumptive Behavior, and Investment Interest - Isma Tersa Septiani; Setyani Sri Haryanti; Yenni Khristiana (Inovasi Analisis Data, 2026)
Purpose—This study examines the influence of personal financial management, consumptive behavior, and investment interest on fintech usage among university students. The study aims to provide empirical evidence on the behavioral and financial factors that shape students’ adoption and use of digital financial services. Design/methodology/approach—This study adopts a quantitative explanatory design. Primary data were collected through a structured questionnaire distributed to 100 active university students who had experience using fintech services. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS to evaluate the measurement model, structural model, and hypotheses. Findings—The results show that personal financial management has a positive but insignificant effect on fintech usage. In contrast, consumptive behavior and investment interest have positive and significant effects on fintech usage. The model explains 25.9% of the variance in fintech usage, indicating that students’ fintech usage is driven more by consumption-related behavior and investment motivation than by personal financial management capability. Originality/value—This study contributes to the digital financial behavior literature by integrating personal financial management, consumptive behavior, and investment interest into a single fintech usage model. Implications—Universities, fintech providers, and policymakers should strengthen digital financial literacy, spending control, investment education, and risk awareness among students.